Desain Bahan Ajar Bahasa Arab Berbasis Konstruktivisme untuk Mahasiswa Non-Pendidikan Bahasa Arab - Baity, Anggi Nurul; Azizah, Sururil; Muna, Fitriah Nailul (STAINI Press, 2025)
Arabic language learning for students in non-Arabic Education programs faces challenges in creating meaningful and relevant learning experiences. Teaching materials, as one of the key components in learning, often focus more on theory and memorization, failing to provide opportunities for students to apply Arabic in everyday contexts. Therefore, this study aims to design constructivist-based teaching materials that can enhance students' understanding and skills in Arabic. This research uses a qualitative method, conducted at the Faculty of Tarbiyah, IAIN Kediri, which consists of nine different study programs. By using techniques such as observation, questionnaires, and interviews with students and lecturers, the study deeply analyzes the teaching materials used, the obstacles faced, and the proposed design of teaching materials based on constructivist theory. The results show that the current teaching materials are not contextual and do not support practice-based learning. The main obstacles lie in the lack of variation in teaching methods and the suboptimal use of materials in connecting theory with real-world application. The proposed constructivist-based teaching materials emphasize interactivity, cultural relevance, and the use of technology to create a more engaging and effective learning experience.